Necesidad de reformar el procedimiento del divorcio por mutuo consentimiento para estar acorde al nuevo modelo de gestión - Guerrero Navarro, Emilio José (2014)
The consensual or also well-known divorce as divorce for mutual consent, is an act of the free will of people, if we take into account that the marriage is a solemn contract in which intervenes the capacity and absolute will of the interested ones, they are them same who can cancel of this contract according to its convenience or to have finished its mutual interests. The velocity and procedural agility are in crisis in our judicial system, due to the slowness and represamiento of causes; brought by the model novísimo of management implemented by the current Council of the Judicature; that is not more than, a resorteo of processes in the judicial new units that don't dispatch absolutely anything and that for a simple one written they delay up to three months, what carries of course that also the divorce processes for mutual consent inmersos is seen in this juridical lethargy, since in a consensual divorce valuable a lot of time is used that well can be devoted to other judicial matters; if it is a declaration of the will of the spouses of finishing a contract to which they consent in a free and voluntary way, it cannot be restrictive the time that anything even has to see when children don't exist of for half, for that that the judge's intervention or notary is simply limited to declare that will and in consequence, the judge of the family, civil, not a notary, because the notaries don't have anything to solve, worse to dictate a sentence, they don't sentence they feel records, situation with which don't agree, because alone the judges solve and in the mutual divorce there is not anything to solve but alone to approve in sentence the agreement of wills. On the other hand the Judges of the Judicial Specialized Unit of the Family, Woman, Childhood and Civil Adolescence of the Canton Loja, even the gentlemen Notaries, when dictating their resolution or sentence in the trials of consensual divorce, when children don't exist smaller than for half, we consider that they are acting without competition, since the authority that gives faith of the contract of the marriage's celebration, is the Boss of the Civil Registration, and it is this same who well he/she can give faith of the will of getting divorced to the parts that want it to make for mutual agreement, since the marginación of the marriage's breakup, is carried out it before the same Boss of Civil Registration; however to effects of legality they are not the judges who should approve the agreement in sentence, the notaries. He/she has been able to observe in many cases, when in the procedure of the processes of consensual divorce, like they expand the times, either for the mere whim of one of the parts or for personal interests, they have not appeared to the audience or if they have converged they have not simply accepted, not the fact of getting divorced, but the economic interest, having as consequence the loss of time, economic, social, moral and psychological damages, as well as for the procedural excessive load in the civil environment, what causes a represamiento that he/she forces to fix audiences for three or four later months; situation that has not been solved favorably in our country, spite that it has been included the gentlemen notaries in this purpose but with the same absurd obstacles that worsen the procedure instead of improving. Through this work, treatment of looking for the feasible way, of establishing a procedure adapted in the one that reduces the times to this type of processes, what will allow saving of economic resources, human resources as much to the user as to the judicial function; and what is fundamental, is allowed to use the principles of velocity and procedural economy that consist in the law but that they are not being applied, in the form and for what you/they were created. Likewise the purpose undoubtedly pursues with this investigation, it is to transfer the unique and exclusive competition to the Judge of the Family, so that this official is who administering justice, be who it solves the voluntary agreement of people or solve the will of getting divorced, for mutual agreement when there are not smaller children, in order to activate or to shorten the term of the civil procedure and to eliminate them of the Notarial Law, since the alone gentlemen notaries give faith and they don't solve neither they can approve this consensual divorce. In the face of this reality, and in order to precautelar that mistaken approaches that attempt against the principles of velocity and procedural economy, in the divorce processes for mutual consent when children don't exist smaller than for half, we have developed the present it contributes academic that contains a robust study of the juridical legal mark that aids the invoked principles; the analysis of cases in those that you has proceeded unconstitutionally, forcing the same ones; the signalization of the serious consequences that of they are derived it; the most outstanding conclusions and recommendations, and among last o'clock, the most important thing, a preliminary design of reformations guided to guarantee those injured rights that we worry about.